20E-induced Kr-h1 expression facilitates developmental transitions depending on chromosome accessibility of BR-C enhancers - Shihui Long; Yongyu Qiu; Tong Lin; Shumin Huang; Wenhao Zhang; Suning Liu; Ling Tian; Subba R. Palli; Sheng Li; Kang Li (Proceedings of the National Academy of Sciences, 2025)
Transcription factors and histone modification-mediated chromatin accessibility coordinately regulate spatiotemporal expression of genes that control growth and development. It is well documented that juvenile hormone-activated Kr-h1 antagonizes 20-hydroxyecdysone (20E)-induced expression of the pupal specifier BR-C to sustain larval status in holometabolous insects. Here, we revealed that during the larval–prepupal transition in Drosophila melanogaster , the 20E-activated Kr-h1-BR-C axis is a prerequisite for wing disc morphogenesis. Mechanistically, 20E-EcR/USP-Met-Tai directly activates Kr-h1 that upregulates BR-C expression via the positive Kr-h1 binding sites (PKBS) in the BR-C enhancers. Furthermore, we showed that 20E-induced H3K27 acetylation increases chromatin accessibility of the PKBS-containing enhancers, facilitating the maximum of BR-C expression that promotes developmental transitions. Collectively, in response to different hormone stimuli, a single transcription factor either negatively or positively regulates the expression of the same target gene depending on chromatin accessibility of its different enhancer regions, thus manipulating distinct developmental events.